Regeneration of the Nervous Anam Community of the Lembak Tribe : Comparison of the Organizational Culture of the Nervous Anam Group of Lembak Panorama And Lembak Central Bengkulu - Idham Adi Wijaya; Iwan Kurniawan Subagja; Azis Hakim (Dinasti Publisher, 2026)
Regeneration of the Syaraful Anam Community of the Lembak Tribe (Comparison of Organizational Culture of the Panorama Syaraful Anam Lembak and Lembak Central Bengkulu Groups)